Feeding of sour colostrum to dairy calves - Sukumaran M V (Department of Dairy Science, College of Veterinary and Animal Sciences, 1977)
A study was undertaken to compare the physiological status and performance of the calves fed fermented colostrum for a period of 30 days with those reared on whole milk and also to find out the changes in the properties and composition of bovine colostrum stored at room temperature for 10 days. The colostrum required for feeding the calves was obtained by collecting the first 10 milkings of individual cows after calving and stored at room temperature for 10 days to undergo natural fermentation.